The Effect of Testosterone on Cardiovascular Disease and Cardiovascular Risk Factors in Men: A Review of Clinical and Preclinical Data - Hargun Kaur; Geoff H. Werstuck, PhD (CJC Open, 2021)
Cardiovascular disease (CVD) is the leading cause of death worldwide. The effects of testosterone, the primary male sex hormone, on cardiovascular risk have been of special interest due to the increased risk of CVD in men. Although it is well established that testosterone levels decline and cardiovascular mortality increases with age, the association between testosterone and CVD remains unclear. Observational and randomized studies on the effects of endogenous and exogenous testosterone have produced conflicting data, and meta-analyses have been inconclusive, suggesting significant study heterogeneity. Despite a lack of adequately powered randomized controlled trials, large observational studies in the early 2010s led to advisories on the use of testosterone replacement therapy. Similar advisories have been mandated for certain types of androgen deprivation therapy. Additional research suggests that testosterone shortens the heart-rate–corrected QT interval, improves glycemic control, induces vasodilation, is prothrombotic, and has anti-obesity effects, whereas associations with atherosclerosis and inflammation are less clear. Despite inconclusive evidence on cardiovascular risk and inconsistencies among clinical practice guidelines, millions of men continue to use testosterone replacement and androgen deprivation therapy. In addition to summarizing clinical and preclinical data, this review provides insight on potential mechanisms of action of testosterone on CVD, applications of this knowledge to clinical settings, and avenues for future research. Résumé: Les maladies cardiovasculaires (MCV) sont la principale cause de décès dans le monde. Les effets de la testostérone, principale hormone sexuelle masculine, sur le risque cardiovasculaire ont suscité un intérêt particulier en raison du risque accru de MCV chez les hommes. S'il est bien établi que le taux de testostérone diminue et que la mortalité cardiovasculaire augmente avec l’âge, l'association entre la testostérone et les MCV demeure obscure. Les études d'observation et à répartition aléatoire sur les effets de la testostérone endogène et exogène ont donné des données contradictoires, et les méta-analyses n'ont pas été concluantes, laissant entrevoir une hétérogénéité importante des études. Malgré un manque d'essais comparatifs à répartition aléatoire, de vastes études d'observation réalisées au début des années 2010 ont conduit à formuler des avis sur l'utilisation du traitement de substitution de la testostérone. Des avis similaires ont été demandés pour certains types de traitements antiandrogéniques. D'après d'autres recherches, la testostérone raccourcirait l'intervalle QT corrigé en fonction de la fréquence cardiaque, améliorerait la maîtrise glycémique, provoquerait une vasodilatation, exercerait un effet prothrombotique et aurait des effets anti-obésité; en revanche, le lien avec l'athérosclérose et l'inflammation est moins claire. Malgré des preuves peu concluantes sur le risque cardiovasculaire et des incohérences quant aux directives de pratique clinique, des millions d'hommes continuent de recourir à des traitements de substitution de la testostérone et antiandrogéniques. En plus de résumer les données cliniques et précliniques, cette analyse donne un aperçu des modes d'action potentiels de la testostérone sur les MCV, des applications de ces connaissances en contexte clinique et des pistes de recherches futures.